1994
DOI: 10.1590/s0074-02761994000400021
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour and stridulation during mating in Triatoma infestans (Hemiptera: Reduviidae)

Abstract: Factors affecting mating behaviour in the bug Triatoma infestans were quantitatively studied in the laboratory. Experimental conditions were established so that the probability of copulation increased with the time elapsed since the first adult meal. Copulatory attempts by males did not vary as a function of time, but rejections by females became significantly less frequent with the post feeding time. Non-receptive females displayed four types of rejection behaviour, i.e. flattening, stridulation, evasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 0 publications
7
42
1
6
Order By: Relevance
“…We found that the female determines the occurrence of a copula, given that it could be receptive or non-receptive to the mating attempts performed by males as it was observed in other triatomines (Manrique & Lazzari 1994). If non-receptive, it could refuse the male through different behaviours.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…We found that the female determines the occurrence of a copula, given that it could be receptive or non-receptive to the mating attempts performed by males as it was observed in other triatomines (Manrique & Lazzari 1994). If non-receptive, it could refuse the male through different behaviours.…”
Section: Resultsmentioning
confidence: 61%
“…Males of P. megistus are the sex that actively performs the approximation of the couple, as in all triatomines studied to date. Manrique and Lazzari (1994) studying T. infestans, observed that these insects do not remain joined through their genitalia after the copula, but separate immediately after the male descends from the female. This behaviour allows the occurrence of successive copulas, aided by the fact that couples of this species apparently emit a pheromone that promotes the aggregation of males around the copulating pair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, activation of the NO/cGMP pathway has been able to inhibit sound production provoked by stimulation of muscarinic receptors in the central complex (Wenzel et al 2005). T. infestans possesses a well-developed stridulatory organ (Di Luciano 1981), and sound production has been related to mating behavior (Manrique and Lazzari 1994). Although the source of NOS-LI in the central body has not yet been identified, and since the function of this neuropil is unknown in T. infestans, NO release in this neuropil might be related to the control of sound production.…”
Section: Distribution Of Nos-limentioning
confidence: 99%